Product Innovation, Organizational Ambidexterity, and Marketing Performance of SMEs During Crisis Recovery: Evidence from the Food and Beverage Sector in Indonesia. - Dody Suhermawan (PT. Mawadaku Sukses Solusindo, 2026)
Micro, Small, and Medium Enterprises (MSMEs) constitute a strategic pillar of economic resilience and inclusive growth in emerging economies, particularly in Indonesia. Despite their substantial contribution to employment generation, regional development, and national income, MSMEs remain highly vulnerable to environmental turbulence, especially during periods of economic disruption such as the COVID-19 pandemic. This study investigates the relationship between product innovation, organizational ambidexterity, and marketing performance among SMEs operating in the food and beverage processing sector in Serang City, Banten Province. Specifically, the study examines the direct influence of product innovation on marketing performance, the effect of product innovation on organizational ambidexterity, the impact of organizational ambidexterity on marketing performance, as well as the mediating and moderating roles of organizational ambidexterity. A quantitative explanatory approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from 170 SMEs selected through random sampling based on predefined business criteria. The findings reveal that product innovation significantly enhances marketing performance and organizational ambidexterity. Organizational ambidexterity also exerts a strong positive influence on marketing performance and acts as a significant mediating mechanism in the innovation–performance relationship. However, the moderating effect of organizational ambidexterity weakens the direct relationship between product innovation and marketing performance. The study highlights the strategic importance of balancing exploratory and exploitative organizational capabilities in strengthening SME competitiveness under uncertain business conditions. The findings contribute to strategic management and marketing capability literature while offering managerial insights for SME sustainability, adaptive innovation, and market resilience in emerging economies.